How to assess children's virtue literacy: methodological lessons learnt from the Knightly Virtues programme. Issue 1 (2nd January 2016) - Davison, Ian; Harrison, Tom; Hayes, Dan; Higgins, Jenny
Abstract: Character education is of growing importance in educational discourse. The Knightly Virtues programme draws on selected classic stories to teach eight moral virtues to nine- to 11-year-olds; it has proved to be hugely popular with UK schools. A finding of the trial was the different levels of 'virtue literacy' in faith and non-faith schools. This article outlines the key features of this trial which yielded the positive results and details its methodological strengths and potential shortcomings. Overall, statistical concerns are less problematic than the practical concerns of running trials designed to measure the impact of character education interventions. Of greatest theoretical interest is the conflation of general and virtue-specific literacy; in addition, we tease apart differences in understanding and motivation. The article highlights and discusses the challenges of running trials designed to measure character education, as well as providing insights into promising methodological approaches.